A dança e a terapia assistida por cavalos no transtorno do espectro autista: ensaio clínico sequencial aleatório cego - Santos, Caroline Souza (2017)
Autism Spectrum Disorder (ASD) is caracterized by social interaction, communication and behavior commitments. The aim of the study was investigate the influence of dance, and Equine-Assisted Therapy (EAT) in children with ASD. It is a cross over clinical trial with five participants allocated in three groups: Dance, EAT, Dance & EAT. The following measures were used before and after the interventions: Functional Independence Measure (FIM), World Health Organization Disability Assessment Schedule (WHODAS) 2.0 version, and Childhood Autism Rating Scale (CARS). It was evidenced reduction in ASD graduation (p<0.03); increase in functional independence (p<0.03), social participation (p<0.04), psychosocial adjustments (p<0.02), and communication (p<0.01). The proposals contributed for independence and relationship in TEA.